Social Importance of Human Life and its Protection: A Comparative Study from Islamic and Un-Islamic Perspectives - Dr Amjad Hayat (jihat-ul-islam, 2024)
Society is derived from two words of Sanskrit language: ‘sim’ and ‘aaj’. ‘Sim’ means together or together, while ‘aaj’ means to be united. So, the literal meaning of society is to stay together. The significance of social engagement is also endorsed by today’s global village that despite several advance developments, the states of the world seem to need each other. To fulfill these needs, the inevitability of human relations and connections are the basic factors of human society. The protection of humanity, its dignity and wealth are essential for its existence and survival. Due to dignity of mankind, the act of killing a man is considered the killing of whole mankind in Islam. The social importance of human life in the light of Quran and Prophet's life is crystal clear that whether it is a Muslim or a non-Muslim, the protection of both is required. Allah Almighty and His Messengers ordered to maintain justice in society. All should be equal in the eyes of the law and one's favoritism can herald danger to human life. The Bible says: “And at that time, I urged your judges that you should hear the cases of your brothers and make judgments with justice, whether it is a case with a man, whether he is an Israelite or a foreigner, not to favor anyone while judging”. The society, whether it is human or Islamic has no other connection except for common human rights and relationship. In view of this, this paper has been compiled, in which a comparative social study has been presented from Islamic and non-Islamic perspectives to address the issue of protection and dignity of mankind.